Overview of the information retrieval features of twenty digital libraries - Chowdhury, G.G. (2000)
Reviews the information retrieval features of 20 digital libraries chosen from around the globe. Describes briefly, the features of the chosen digital libraries in terms of their nature and content. Indicates the unique features of some digital libraries. Suggests major areas of research that would improve the information retrieval features of the future digital libraries.